Challenges of Diagnosis and Treatment Choice in Riedel‘s Fibrosing Thyroiditis: Clinical Case Examples - M. G. Davydovich; R. V. Ipaeva; K. P. Derevyanko (Креативная хирургия и онкология)
Background. Clinically distinct Riedel’s fibrosing thyroiditis is extremely rare, accounting for only 0.05 % of histologically verified thyroiditis cases, as follows from the real clinical practice and literature. Classic Riedel’s thyroiditis is typified by a marked compression syndrome, which may lack at initial disease stages. A problematic verification often conduces to a diagnostic and, especially, therapeutic malpractice, as illustrated by the two hereby analysed clinical cases.Materials and methods. The article presents two clinical cases of fibrosing thyroiditis, specifying the diagnosis and treatment choice in patients with this pathology. Diagnosis verification and therapy correction facilitated a favourable outcome.Results and discussion. Riedel’s fibrosing thyroiditis can be reluctant to diagnosis due to asymptomatic thyroid dysfunction, the lack of strict radiological diagnostic criteria and rarity in clinical practice. This provokes diagnostic and later therapeutic malpractices, which correction permitted a favourable outcome.Conclusion. Since treatment for compression syndrome-aggravated Riedel’s fibrosing thyroiditis is exclusively surgical, it continues posing a challenge as associated with likely severe complications. Essentially, the first treatment stage was inadequate in both cases. In the first case, the patient withdrew a thyroid hormone therapy already in 4 days, which precluded serious iatrogenic complications, while in the second case, the long-term drug misuse had conduced to cardiovascular pathology.